Teachers' beliefs and practices in teaching reading at Islamic secondary schools in Indonesia - Nurkamto, Joko; Drajati, Nur Arifah; Ngadiso, N.; Karlina, Yeni (Universitas Pendidikan Indonesia, 2021)
The importance of English reading skills in developing overall English literacy has made reading instruction one of the primary focuses in Indonesia's English teaching. Regardless of the high value of reading skills, the teaching of reading has not been successful in developing the reading comprehension ability of Indonesian students. This exploratory case study research examines teachers' beliefs and practices in teaching reading in Islamic secondary schools. It focuses mainly on how teachers view good reading instruction and the problems they encounter in teaching reading. Additionally, this paper explores how teachers implement reading instruction in their contexts. Data were obtained from 31 senior Islamic secondary school English teachers from six different provinces in Indonesia. Data collection methods comprised document analysis, participant classroom observation, personal in-depth interviews, written guided reflections, and focus group discussions. The data were analyzed using the constant comparative method. The research findings show that despite admitting the importance of teaching reading in schools, the English teachers of Islamic senior high schools found teaching reading challenging. The teachers identified several problems in reading instruction in their classrooms, such as lack of strategies to teach vocabulary, limited repertoire of strategies to teach reading, the use of teaching materials, and improving students' reading motivation and autonomy. As a result, they have not been able to implement classroom practices that effectively develop students' reading comprehension. This issue calls for the innovation and development of teaching reading strategies to improve reading instruction quality in Islamic secondary schools in Indonesia.